Final answer:
We can use mathematical induction to prove the given statement: 1/2 +...+ 1/2ⁿ = 2ⁿ-1/2ⁿ.
Step-by-step explanation:
We can use mathematical induction to prove the given statement:
Step 1: Base case - Let's check if the statement is true for n = 1.
Substituting n = 1 into the given expression, we get:
1/2 = 2^1-1/2^1 = 1/2
So, the base case holds.
Step 2: Inductive step - Assume that the statement is true for some positive integer k, i.e.,
1/2 + ... + 1/2^k = 2^k-1/2^k
Now, we need to prove that the statement is true for k+1:
1/2 + ... + 1/2^k + 1/2^(k+1) = 2^(k+1)-1/2^(k+1)
To prove this, we can rewrite the expression on the left-hand side as:
2^k-1/2^k + 1/2^(k+1)
Combining the fractions, we get:
(2^k-1 * 2)/(2^k * 2)
Simplifying, we have:
(2^(k+1)-2)/(2^(k+1))
Which is equal to:
2^(k+1)-1/2^(k+1)
Thus, the statement holds for k+1 as well.
Therefore, by the principle of mathematical induction, the statement holds for all positive integers n.